2016
DOI: 10.1093/ntr/ntv080
|View full text |Cite
|
Sign up to set email alerts
|

“Direct Dripping”: A High-Temperature, High-Formaldehyde Emission Electronic Cigarette Use Method

Abstract: Due to the higher temperatures attained, DDAs are inherently likely to produce high toxicant emissions. The diversity of ECIG use methods, including potential off-label methods, should be considered as ECIG regulatory efforts proceed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
117
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 27 publications
(43 reference statements)
2
117
0
1
Order By: Relevance
“…Although the number of fires and explosions from E-Cig devices has increased since inception, interestingly, many of these instances occurred while the device was being charged and are still considered rare (https://www.usfa.fema.gov/downloads/pdf/publications/ electronic_cigarettes.pdf). An additional, behavioral modification that has developed among E-Cig users is "dripping," which entails dripping e-liquid directly on the atomizer (i.e., the heating element) and inhaling the resultant vapor, which is supposed to give the largest amount of nicotine delivery possible with current E-Cig devices (146). Parameters of E-Cig emission, such as aerosol size, mass output, and chemical composition, vary by device and e-liquid types and are predicted to impact the user's exposure to the E-Cig aerosol.…”
Section: Tissue/cell Type Effectsmentioning
confidence: 99%
“…Although the number of fires and explosions from E-Cig devices has increased since inception, interestingly, many of these instances occurred while the device was being charged and are still considered rare (https://www.usfa.fema.gov/downloads/pdf/publications/ electronic_cigarettes.pdf). An additional, behavioral modification that has developed among E-Cig users is "dripping," which entails dripping e-liquid directly on the atomizer (i.e., the heating element) and inhaling the resultant vapor, which is supposed to give the largest amount of nicotine delivery possible with current E-Cig devices (146). Parameters of E-Cig emission, such as aerosol size, mass output, and chemical composition, vary by device and e-liquid types and are predicted to impact the user's exposure to the E-Cig aerosol.…”
Section: Tissue/cell Type Effectsmentioning
confidence: 99%
“…Of concern, existing evidence, though limited, suggests that dripping e-liquids may lead to higher levels of nonnicotine toxicant emissions. 6 Our evidence suggests that male students, white students, those who had tried multiple tobacco products, and those who used e-cigarettes on more days in the past month were more likely to report using e-cigarettes for dripping behaviors. These results suggest that youth who use dripping may be those who are more familiar with and have experience with using multiple tobacco products, including e-cigarettes.…”
Section: Discussionmentioning
confidence: 72%
“…com/ art-dripguide-vaping/ ). Although there is no evidence on the prevalence rates or toxicity of this behavior among adults or youth, Talih et al 6 have shown that dripping e-liquids directly onto the e-cigarette atomizers could expose users to high temperatures and toxic chemicals such as aldehydes. Moreover, Kosmider et al 7 have shown that exposure of e-liquids to high temperatures results in significant increases in the levels of formaldehyde, acetaldehyde, and acetone in the vapors.…”
mentioning
confidence: 99%
“…Some manufacturers have indicated that the chamber temperature is kept below 100°C, thus the toxic acrolein degradation caused by the high temperature is avoided (28). However, some studies have reported that the temperature exceeds 350°C when the solution in the cartridge is heated by the battery (8,48).…”
Section: Acrolein Diethylene Glycol and Formaldehydementioning
confidence: 99%
“…Besides acrolein, it is another important situation that formaldehyde which is a toxic compound due to high temperatures can form in e-cigarettes that are especially used directly with dripping technique (48). Diethylene glycol that is a toxic chemical used as an anti-freeze was identified in an e-cigarette sample investigated in a research conducted by the FDA (5).…”
Section: Acrolein Diethylene Glycol and Formaldehydementioning
confidence: 99%